2011
DOI: 10.1371/journal.pgen.1002085
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Dynamics in Human Induced Pluripotent Stem Cells over Time

Abstract: Epigenetic reprogramming is a critical event in the generation of induced pluripotent stem cells (iPSCs). Here, we determined the DNA methylation profiles of 22 human iPSC lines derived from five different cell types (human endometrium, placental artery endothelium, amnion, fetal lung fibroblast, and menstrual blood cell) and five human embryonic stem cell (ESC) lines, and we followed the aberrant methylation sites in iPSCs for up to 42 weeks. The iPSCs exhibited distinct epigenetic differences from ESCs, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
240
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(266 citation statements)
references
References 48 publications
21
240
3
2
Order By: Relevance
“…11,12 One must use caution when analyzing epigenetic aberrations in imprinting disease iPSCs because the process of iPSC generation is associated with epigenetic dynamics that may bias interpretation. 13 However, iPSCs with in vitro multipotency have been an invaluable tool to clarify molecular mechanisms as a simulator of developmental defects. 14,15 PRACTICAL ADVICE BEFORE YOU BEGIN These exemplary cases certainly make us feel hopeful that we can apply patient iPSCs to various diseases.…”
Section: Imprinting Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 One must use caution when analyzing epigenetic aberrations in imprinting disease iPSCs because the process of iPSC generation is associated with epigenetic dynamics that may bias interpretation. 13 However, iPSCs with in vitro multipotency have been an invaluable tool to clarify molecular mechanisms as a simulator of developmental defects. 14,15 PRACTICAL ADVICE BEFORE YOU BEGIN These exemplary cases certainly make us feel hopeful that we can apply patient iPSCs to various diseases.…”
Section: Imprinting Disordersmentioning
confidence: 99%
“…In addition to these standard quality controls, profiling of RNA expression, DNA methylation and glycans can be added for monitoring when necessary. 10,13,36,37 These comprehensive analyses would also elucidate pathogenic states such as aberrant genomic methylation and gene expression of patient iPSCs.…”
Section: Quest For Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…A study using human iPSCs derived from pancreatic islet beta cells has shown that these iPSCs can be distinguished by their epigenetic profiles from other pluripotent stem cells and that they had increased ability to differentiate into insulinproducing cells [46]. On the other hand, studies from both mouse and human iPSCs have suggested that the epigenetic memory is likely to be observed at early passages of iPSCs and can be erased through continuous passaging [45,47]. Functional studies have also shown that with improved differentiation conditions, iPSCs of diverse origins can be differentiated into functional cell types such as neural cells and hepatic cells at comparable efficiencies even though they can be distinguished by epigenetic profiles [48,49].…”
Section: Epigenetic Memorymentioning
confidence: 99%
“…This approach enabled us to perform an extensive comparison of iPSC-derived DA neurons with primary mDA neurons (including varying developmental stages) as far as their genetic and epigenetic profiles are concerned. We particularly focused on DNA methylation, since reprogramming of somatic cells towards pluripotent cells and subsequent differentiation into DA neurons must entail massive changes in DNA methylation patterns in specific genomic loci [47][48][49][50]. This type of characterization, which was based on the ability to analyze purified Pitx3-GFP DA neurons, enabled us to determine a close similarity in terms of DNA methylation patterns between iPSC-derived DA neurons and primary DA neurons and provides novel insight in cell type specific de novo methylation during in vitro differentiation (Roessler et al, manuscript in preparation).…”
Section: Mouse Ipscs As Crucial Model Systemmentioning
confidence: 99%